PEMENUHAN OBAT COVID-19 DI INSTALASI FARMASI PROVINSI KALIMANTAN SELATAN - Laeliyatun Ikrimah; Abdul Rahem; Anita Purnamayanti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Covid-19 pandemic has not ended and reach its peak in July 2021. The handling of this pandemic is carried out with logistical support for treatment as therapy. Antivirus and antibiotic widely used are Oseltamivir75mg, Favipiravir 200mg and Azithromycin500 mg. The purpose of this study was to determine the need and fulfillment of these medicines in 13 cities and health facilities in South Kalimantan. This study uses observational methode with a total sample of the need and fulfillment of these drugs in July 2021 at IFP South Kalimantan which includes IFK in 13 cities and health facilities that serve the handling of COVID-19. The method of analysis used is descriptive analysis with the most usage and the average percentage fulfillment of needs.The result showed that IFP South Kalimantan could meet about 51,35% of the need for Oseltamivir 75mg, 65,71% for Favipiravir 200mg and 38,68% Azithromycin 500mg from the total needs of 13 cities in South Kalimantan. The most commonly used oseltamivir 75mg and azithromycin 500mg were IFK Banjarmasin, Tanah Bumbu and Kotabaru. This indicates that Covid-19 severity was mild in that cities. The most use of favipiravir is Ulin Hospital, Idaman Hospital and Ansari Shaleh Hospital as 3 referral hospitals in the cities of Banjarmasin and Banjarbaru. It is indicate of moderate to severe COVID-19 that requiring hospital treatment. Conclusion of this study are the fullfill of Favipiravir 200mg and Oseltamivir 75mg are more than 50% of IFK need in 13 cities.